The influence of entrepreneurs’ culture and ethnicity on firms’ degree of hybridity - Angulo-Ruiz, Fernando; Muralidharan, Etayankara (My University, 2023)
Hybrid businesses that combine profit and social objectives at their core play an important role in their communities. In this article, we use insights from paradox theory to examine the influence of entrepreneurs’ cultural value orientations and ethnicity on distinct forms of hybrid businesses. We use a unique random sample of international small- and medium-sized privately owned businesses in Canada. After controlling for alternative explanations and using propensity scores to match the samples of Indigenous and non-Indigenous entrepreneurs, we consistently find that entrepreneurs’ self-expression values and Indigenous ethnicity are positively associated with a higher degree of hybridity in the businesses they start. Our findings contribute to the conversations on the micro-foundations of organizational paradox and to the literature on the factors that influence different hybrid organizational forms. Besides, our findings also add to the literature that examines hybridity in the context of internationalized businesses. The rationality and culture of the entrepreneur affect organizational paradox. Entrepreneurs with self-expressive values and identified with an Indigenous ethnicity have higher proclivities to form ideal hybrids and embrace paradoxical organizational forms.
Keywords: degree of hybridity; hybrid firms; hybrid forms; Indigenous businesses; non-Indigenous firms; paradox; self-expression values; traditional values